1997
DOI: 10.1105/tpc.9.8.1251
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and cytogenetic analyses of stably and unstably expressed transgene loci in tobacco.

Abstract: To study the influence of genomic context on transgene expression, we have determined the T-DNA structure, flanking DNA sequences, and chromosomal location of four independent transgene loci in tobacco. Two of these loci were stably expressed in the homozygous condition over many generations, whereas the other two loci became unstable after several generations of homozygosity. The stably expressed loci comprised relatively simple T-DNA arrangements that were flanked on at least one side by plant DNA containing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
106
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(109 citation statements)
references
References 52 publications
3
106
0
Order By: Relevance
“…Molecular analyses revealed that this line contained an elevated number of transgene copies (> 10) and extra-border vector sequences. While both of these conditions are often associated with gene-silencing events [22,23,27], the fact that 25 lines (out of the 65 transformed lines) contained extra-border sequences but still expressed the transgene would suggest that, in poplar, the presence of Ti-plasmid sequences is not a major factor in influencing transgene expression. RT-PCR experiments performed on the silent line revealed that both the uidA gene and the selection gene nptII were transcribed suggesting that silencing occurs at the posttranscriptional level.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular analyses revealed that this line contained an elevated number of transgene copies (> 10) and extra-border vector sequences. While both of these conditions are often associated with gene-silencing events [22,23,27], the fact that 25 lines (out of the 65 transformed lines) contained extra-border sequences but still expressed the transgene would suggest that, in poplar, the presence of Ti-plasmid sequences is not a major factor in influencing transgene expression. RT-PCR experiments performed on the silent line revealed that both the uidA gene and the selection gene nptII were transcribed suggesting that silencing occurs at the posttranscriptional level.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic engineering of plants sometimes results in transgene silencing after integration into the host genome, which may be related to a defence mechanism against foreign DNA expression [28]. In fact, when analysing the effects of the surrounding genomic environment on transgene expression, one must also consider the potentially broader impact of the genome organization of the host plant with respect to the chromosomal distribution of structural genes, abundance, diversity, arrangement of repetitive DNA and the constitution of sub-genomes in polyploids [24]. Transgene silencing has been reported for diploid, autopolyploids and allopolyploids [25,29].…”
Section: Discussionmentioning
confidence: 99%
“…Reliable and stable expression of transgenes as well as the characterization and field adaptation of transgenic lines are prerequisites for the successful application of gene technology. Many papers have reported significant variability in the behaviour of the same transgene in different lines [24]. Loci that appear to be stably expressed initially can become progressively silenced over several generations [25].…”
Section: Introductionmentioning
confidence: 99%
“…In comparison with the previous systems reported for sugar beet transformation (Joersbo et al, 1998;Ivic-Haymes and Smigocki, 2005), our method was characterized by higher transformation efficiency, a lower transgene copy number in plants, and a shorter period to recover transgenic plants. Furthermore, low transgene copies reduce the possibility of gene silencing and increase the stability of the transgene (Iglesias et al, 1997;Li, 2008).…”
Section: Agrobacterium-mediated Transformation Of Sugar Beet Plantsmentioning
confidence: 99%